Predictors of nonresponse to intravenous immunoglobulin therapy in Kawasaki disease - Hyo Min Park; Dong Won Lee; Myung Chul Hyun; Sang Bum Lee (Korean Pediatric Society, 2013)
PurposeIt has been reported that 10% to 20% of children with Kawasaki disease (KD) will not respond to intravenous immunoglobulin (IVIG) treatment. In this study, we aimed to identify useful predictors of therapeutic failure in children with KD.MethodsWe examined 309 children diagnosed with KD at the Kyungpook National University Hospital and the Inje University Busan Paik Hospital between January 2005 and June 2011. We retrospectively reviewed their medical records and analyzed multiple parameters in responders and nonresponders to IVIG.ResultsAmong the 309 children, 30 (9.7%) did not respond to IVIG. They had significantly higher proportion of neutrophils, and higher levels of aspartate aminotransferase, alanine aminotransferase (ALT), total bilirubin, and N-terminal fragment of B-type natriuretic peptide than did responders. IVIG-nonresponders had a significantly longer duration of hospitalization, and more frequently experienced coronary artery lesion, and sterile pyuria. No differences in the duration of fever at initial treatment or, clinical features were noted.ConclusionTwo independent predictors (ALT≥84 IU/L, total bilirubin≥0.9 mg/dL) for nonresponse were confirmed through multivariate logistic regression analysis. Thus elevated ALT and total bilirubin levels might be useful in predicting nonresponse to IVIG therapy in children with KD.